Efek Mediasi Profitabilitas Pada Pengaruh Green Accounting Terhadap Nilai Perusahaan - Nugroho, Wawan Cahyo (E-Jurnal Akuntansi; Vol 33 No 3 (2023), 2023)
The issue of environmental preservation is the company's goal for the welfare of stakeholders. The research aims to examine and analyze the effect of green accounting on firm value through profitability variables and contribute to helping solve company problems in making decisions related to green accounting and firm value. The study used 132 samples of observations from 22 mining companies listed on the IDX for 6 years. Data analysis techniques use multiple linear regression and sobel analysis. The results of green accounting research have a significant positive effect on profitability and firm value, because companies registered with the PROPER program are considered to care about the environment so as to ensure business continuity and increase firm value. Profitability has a significant positive effect on firm value and profitability is able to mediate the relationship between green accounting and firm value because companies that earn profits will provide positive information to investors and implement environmental costs in financial statements. Keywords: Green Accounting; Profitability; Firm Value